A Rare Case of Leptomeningeal Signet-Ring Cell Melanomatosis with Unknown Primary Mimicking Leptomeningeal Carcinomatosis - Martin, Sarah E; Qiu, Michelle L; Fabiano, Andrew J; Chen, Frank; Qiu, Jingxin (North American Journal of Medicine and Science, 2016)
We present a first case of a 63-year-old man clinically diagnosed with leptomeningeal carcinomatosis, who upon postmortem examination was found instead to have leptomeningeal melanomatosis with signet-ring cell features and unknown primary. This patient presented with no known history of cancer or skin lesions and six months history of anorexia, weight loss and fatigue, followed by two weeks of confusion and difficulty with speaking and ambulating. Brain MRI showed multiple variably sized contrast-enhancing lesions and diffuse abnormal leptomeningeal contrast enhancement. Full body CT imaging revealed no detectable lesions elsewhere in the body. Antemortem CSF cytology was diagnosed as metastatic adenocarcinoma on multiple occasions based upon the signet ring cell morphology. Immunohistochemical studies were not performed because of the scant cellularity. The patient expired despite treatment with Temazolamide, whole brain radiation, and intrathecal methotrexate. Postmortem examination of the brain revealed no gross abnormality. Microscopic examination showed a subdural collection of discohesive tumor cells with marked nuclear pleomorphism, hyperchromasia, and frequent signet-ring or rhabdoid morphology, as well as a striking, diffuse infiltration of tumor cells in the leptomeninges. Intraparenchymal deposits were also seen in many areas. General autopsy also identified tumor metastases in the larynx and testes. Tumor cells were immunoreactive for melanoma markers (S100, Melan-A, Tyrosinase and HMB-45) and negative for cytokeratins and mucin. There is no evidence of primary melanocytic lesion or neurocutaneous melanosis. A diagnosis of leptomeningeal signet-ring cell melanomatosis with unknown primary was rendered. While most patients with metastatic melanoma do have a known history, in a small percentage no primary site is ever identified. We discuss possible etiologies for this phenomenon and emphasize the potential pitfall of signet-ring melanoma clinically and cytologically mimicking adenocarcinoma. Melanoma with signet-ring cell features should be included in the differential diagnosis for cases of presumed adenocarcinoma with unknown primary.